The traditional commons of England and Wales in the twenty-first century: meeting new and old challenges. Issue 2 (1st July 2008) - Short, Christopher
The commons literature makes much of the changes within the traditional land use sectors of developed countries. This largely focuses on the decline of the economic function of commons that threaten their existence, the emergence of multiple use patterns, and the resilience and policy adaptation needed to continue. The situation in England and Wales is used to illustrate that commons are increasingly important to a number of 'new' rural functions and that the associated policy developments may hold an important message for progress towards sustainable multifunctional land management more generally. This article reviews and updates what is meant by the term common land within England and Wales, while outlining its current importance and threats. The commons literature is investigated to see if the approach is useful in revealing the current issues associated with the incorporation of new stakeholders and functions within a traditional structure. Recent changes and developments surrounding the Commons Act 2006 are assessed to see if they are likely to assist in sustaining these commons through the twenty-first century. The article argues that any new approach requires long term planning and a commitment to support local participation among commoners and others who are involved in the governance and management of these areas of land. In order for these challenges to be met there needs to be an understanding of the functions and cultural traditions of common land as well as of the changes in society associated with the decline in traditional agrarian management in developed countries. Such challenges can rarely if ever be achieved through legislation and policy developments, requiring an investment in developing locally based solutions.